Steffen Elmer Jørgensen (ed.): From Scandinavia to America. Proceedings from a Conference held at Gl. Holtegaard. (Odense University Press, 1987). 377 s., 195,20 kr. - Bonderup, Gerda (Historie/Jyske Samlinger, 1989)
-